Exploring first-year university students' learning journals: Conceptions of second language self-concept and self-efficacy for academic writing. (June 2022) - Mendoza, Laura; Lehtonen, Tuula; Lindblom-Ylänne, Sari; Hyytinen, Heidi
Abstract: This qualitative study analyzes first-year university students' conceptions of their second language (L2) self-concept and self-efficacy for academic writing in English. The data consist of learning journals (N = 74), collected at a Finnish university in an English as a medium of instruction (EMI) context. L2 self-concept descriptions included positive, mixed, and negative ends of the continuum as well as stories of change. These descriptions encompassed various contextual mentions including grades, the current EMI context, and social comparison. The self-efficacy beliefs for academic writing reflected a stage of change among the students. The students reporting more positive, emerging self-efficacy described sensations of familiarity with academic writing. In turn, the students reporting low self-efficacy emphasized that academic writing was new and that they needed more guidance and feedback. An analysis of how the L2 self-concept conceptions and self-efficacy beliefs for academic writing co-occurred on an individual level revealed further variation among this group. Nevertheless, the negative L2 self-concept conceptions seemed to co-occur more with low self-efficacy for academic writing. Furthermore, the findings suggest that positive L2 self-concept conceptions may be of help when building self-efficacy for academic writing in English. The implications are discussed on theoretical and pedagogical levels.